2013
DOI: 10.3892/or.2013.2361
|View full text |Cite
|
Sign up to set email alerts
|

The role of the WWOX gene in leukemia and its mechanisms of action

Abstract: Abstract. The WW domain-containing oxidoreductase (WWOX) gene which encompasses the common human fragile site FRA16D has been proposed as a putative tumor suppressor gene, and loss of WWOX expression has been found in several types of solid cancer. As the role of WWOX in human leukemia has not yet been fully elucidated, the present study examined the expression of WWOX in patients with different types of leukemia as well as in leukemia-derived cell lines. Based on the data, WWOX mRNA (WWOX) and protein (Wwox) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
(35 reference statements)
5
22
0
1
Order By: Relevance
“…Similarly, the aberration or absence of WWOX/WWOX expression in primary hematopoietic malignancies has also been reported (11)(12)(13)(14)(15)(16). A recently published study detected the expression of WWOX/WWOX in a small cohort of 38 primary leukemia patients and observed low expression levels (14). Chen et al (13) recently validated the expression of WWOX in ALL, and observed that the mRNA expression of WWOX, fragile histidine triad and tumor protein p73 was significantly lower in the ALL samples compared with the controls.…”
Section: A B Cmentioning
confidence: 79%
See 3 more Smart Citations
“…Similarly, the aberration or absence of WWOX/WWOX expression in primary hematopoietic malignancies has also been reported (11)(12)(13)(14)(15)(16). A recently published study detected the expression of WWOX/WWOX in a small cohort of 38 primary leukemia patients and observed low expression levels (14). Chen et al (13) recently validated the expression of WWOX in ALL, and observed that the mRNA expression of WWOX, fragile histidine triad and tumor protein p73 was significantly lower in the ALL samples compared with the controls.…”
Section: A B Cmentioning
confidence: 79%
“…The role of WWOX/WWOX in leukemia has also been reported, suggesting that WWOX may exert antineoplastic activity in human hematopoietic malignancies (11)(12)(13)(14)(15)(16). Our previous studies have demonstrated that WWOX exerts a role as an tumor suppressor gene in leukemia, inhibiting cell proliferation and promoting apoptosis via binding with p73 and triggering of the mitochondrial pathway (14,15).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The primer sequences for Bcl-2, Bax and GAPDH were previously described [17]. The comparative Ct method was used to calculate the relative expression level of Bcl-2 or Bax as compared with GAPDH.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%